Systematika zelených kokálních řas tříd Chlorophyceae a Trebouxiophyceae - Štenclová, Lenka (Jihočeská univerzita, 2021)
Aim of the review part is to summarize a current situation in the systematics of the green coccal algae, which were traditionally assembled in only one order: Chlorococcales. Their distribution into the lower taxonomical unites (suborders, families, subfamilies, genera) was based on the classic morphological criteria as shape of the cell and characteristics of the colony. Introduction of molecular methods caused radical changes in our insight to the system of green (not only coccal) algae and green coccal algae were redistributed in two of newly described classes: Chlorophyceae a Trebouxiophyceae. Representatives of individual morphologically delimited families, subfamilies and even genera and species were commonly split in several lineages, often in both of mentioned classes. For the practical part, was chosen two problematical groups of green coccal algae: family Oocystaceae and family Scenedesmaceae - specifically its subfamily Crucigenioideae, which were revised using polyphasic approach. Based on the molecular phylogeny, relevance of some old traditional morphological traits was reevaluated and replaced by newly defined significant characteristics.
SYSTEMATICS OF COCCAL GREEN ALGAE OF THE CLASSES CHLOROPHYCEAE AND TREBOUXIOPHYCEAE
Keywords: green algae; systematics; phylogeny; Chlorophyceae; Trebouxiophyceae; Oocystaceae; Crucigenioideae; green algae; systematics; phylogeny; Chlorophyceae; Trebouxiophyceae; Oocystaceae; Crucigenioideae